2017
DOI: 10.1017/s0031182017000415
|View full text |Cite
|
Sign up to set email alerts
|

Simple dialkyl pyrazole-3,5-dicarboxylates show in vitro and in vivo activity against disease-causing trypanosomatids

Abstract: The synthesis and antiprotozoal activity of some simple dialkyl pyrazole-3,5-dicarboxylates (compounds 2-6) and their sodium salts (pyrazolates) (compounds 7-9) against Trypanosoma cruzi, Leishmania infantum and Leishmania braziliensis are reported. In most cases the studied compounds showed, especially against the clinically significant amastigote forms, in vitro activities higher than those of the reference drugs (benznidazole for T. cruzi and glucantime for Leishmania spp.); furthermore, the low non-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Reviriego et al reported the synthesis and antiprotozoal activity of some simple dialkyl pyrazole-3,5-dicarboxylates against Trypanosoma cruzi , Leishmania infantum and Leishmania braziliensis . The diethyl ester 476 showed high efficiency against the mentioned protozoa [ 373 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Reviriego et al reported the synthesis and antiprotozoal activity of some simple dialkyl pyrazole-3,5-dicarboxylates against Trypanosoma cruzi , Leishmania infantum and Leishmania braziliensis . The diethyl ester 476 showed high efficiency against the mentioned protozoa [ 373 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In combination with their favorable drug-like properties, privileged structures or scaffolds are widely used in rational drug design to find new lead compounds or drug candidates [1,2,3]. Pyrazole derivatives represent one of the most active classes of compounds that possess a wide spectrum of biological activities, including antibacterial and antifungal [4,5], antitumor [6,7], anti-inflammatory and analgesic [8,9], antitubercular [10], antiviral [11,12], anti-Alzheimer’s [13,14], α-glucosidase inhibitory [15], anti-diabetic [16], antileishmanial [17,18], anti-malarial [19], radioimaging [20], acaricidal and insecticidal [21,22] activities. As a privileged scaffold, pyrazole has been recently widely used in the design of anticancer agents for a multiple of tumor targets [23].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity data demonstrated that 3g, 3j, and 3m are weak inhibitors of cysteine protease and, therefore, the improvement of trypanocidal activity against intracellular parasites involves other mechanisms of action not yet elucidated. Evidence has shown that, in addition to cruzipain, the iron-dependent superoxide dismutase (Fe-SOD) [46,47] and CYP51 [48] are molecular targets implicated in the trypanocidal activity of the pyrazole derivatives. Thus, it is possible that the trypanocidal activity of promising pyrazole derivatives is associated with mitochondrial dysfunction, as predicted by the pyrazole derivatives distribution in the ADMET analysis, which will be a target of further analysis.…”
Section: Enzyme Activitymentioning
confidence: 99%